1977
DOI: 10.1017/s0022172400056333
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella surveillance with reference to pigs – Cardiff abattoir, 1968–1975

Abstract: Between 1968 and 1975, well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…We have compared these media on several occasions. Not all results have been in agreement with each other (Harvey, Price & Morgan, 1977). We believe that comparisons between selenite and tetrathionate are influenced by the prevalent serotypes in the material (Harvey & Price, 1975), by the material examined, the detailed composition and preparation of the media and whether pre-enrichment or direct enrichment is used.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…We have compared these media on several occasions. Not all results have been in agreement with each other (Harvey, Price & Morgan, 1977). We believe that comparisons between selenite and tetrathionate are influenced by the prevalent serotypes in the material (Harvey & Price, 1975), by the material examined, the detailed composition and preparation of the media and whether pre-enrichment or direct enrichment is used.…”
Section: Resultsmentioning
confidence: 85%
“…Small inocula from the pre-enrichment culture are likely to contain salmonellas capable of multiplying in the enrichment broth (Loeffler, 1906). A high inoculum ratio can, however, be a liability with direct enrichment when large inocula may be necessary, as in the study ofpig faeces using 80 g inocula (Harvey, Price & Morgan, 1977). Under these circumstances we would prefer selenite and/or tetrathionate which can accept large amounts of potentially infected material.…”
Section: Resultsmentioning
confidence: 99%
“…at slaughter (Riley 1970;Edel & Kampelmacher 1976;Harvey, Price & Morgan 1977). These studies have shown that the intestinal tract and mesenteric lymph nodes are frequently infected and provide a source from which salmonella may be spread in the abattoir during evisceration and dressing.…”
Section: Introductionmentioning
confidence: 99%
“…Where large inocula, such as 80 g, are to be introduced into an enrichment medium as in an earlier paper on salmonellas in pig faeces, the R25 broth might not be so efficient as in this study. Both selenite F and Muller-Kauffmann tetrathionate can accept large inocula and might be more suitable media (Harvey, Price & Morgan, 1977).…”
Section: Discussionmentioning
confidence: 99%